Penerapan Filsafat Ilmu dalam Penyusunan Karya Ilmiah - Rizki Hannum; Jihan Fadhilah; Rahma Pratiwi; Adjie Rahim Ramadhan; Siti Mujiatun (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Philosophy of science has an important role in the preparation of scientific work, especially in management science, by providing a conceptual framework that integrates aspects of ontology, epistemology and axiology. This research discusses the application of the philosophy of science in the entire research process, starting from problem formulation, developing a theoretical framework, to presenting findings. The philosophy of science approach allows the selection of relevant research paradigms and valid methods to produce applicable and ethical solutions. In addition, philosophy of science contributes to the development of new paradigms, strengthening research ethics, and increasing creativity in scientific research. By using a literature review approach, this research provides insight into how the philosophy of science supports the development of management science through knowledge validation and systematic methodological testing